Financial planning for post-retirement among Urban Malaysians in Klang Valley / Tan Hoe Kock - Tan, Hoe Kock (2015)
This study examines the extent Malaysians make financial preparations and their readiness for retirement and the predictors of financial planning for post-retirement. The study delved into the concept of financial planning, life-cycle theories of savings, consumption, and investing, and the critical issues surrounding the study of retirement, particularly the financing of consumption during the post-retirement period. Data was collected using questionnaire survey method on urban Malaysians in the Klang Valley areas. A total of 990 questionnaires were distributed to respondents with a 55.2 percent return rate. The results revealed that twelve of the hypotheses and sub-hypotheses were supported and five were not supported. The study found that education, spouse age, home ownership, and current financial resources are significant demographic variables that have a positive relationship with financial planning for post-retirement. There is a significant perception towards financial planning for post-retirement among the older age cohorts (age above 46 years). This difference in perceptions among the different age cohorts could be attributable to younger age cohorts having lower income and higher financial commitments. While the younger age cohorts may be aware of the importance of financial planning, they may choose to defer their saving decisions as they feel that time is still on their side. The study found a positive relationship between consumption and financial planning for post-retirement. Expected retirement age was found to have no moderating effect on the relationship between personal orientations towards retirement planning and financial planning for post-retirement. This finding has important implications for policy makers to spearhead a campaign for a higher level of financial literacy in schools and educational institutions and to inculcate the importance of further savings among young Malaysians in beginning of their career. This is to supplement the expected government pension for the civil servants and the employees provident fund contributions (EPF) for people in the private sector. The policymakers will have to review their economic strategies of relying heavily on private consumption to stimulate domestic economic growth. In view of the high household debts and longer life span now, more Malaysians may not be able to retire at the expected retirement age of 60 years. As the number of older Malaysians is projected to rise to 3.4 million by 2020, this phenomenon has major implications for policy makers to review the existing social security framework for retirees and the pressing need for medical care and housing for Malaysian retirees.